FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN PENOLONG PERSALINAN DI DESA GEMA KABUPATEN KAMPAR TAHUN 2020 - Nevi Susianty; Surisna Okrianti; Ayu Rahmawati (Journal of Health Science and Physiotherapy, 2022)
Delivery assistance by midwives is one strategy regarding maternal and child health problems. In Indonesia, the use of delivery assistance by midwives in the community is still low compared to the expected indicators. The purpose of this study was to analyze the factors related to the selection of birth attendants in Gema Village, Kampar Kiri Hulu I Public Health Center in Kampar Regency in 2020. The design of this study was descriptive analytic with a cross sectional approach. The population in this study were all mothers who gave birth in the Work Area of ​​the Kampar Kiri Hulu I Health Center from January to December 2020 totaling 43 people. All populations were sampled in this study. The measuring tools used are questionnaires and checklist sheets. The analysis used is univariate and bivariate. The results of the study concluded that some mothers chose health workers as birth attendants, with less knowledge, negative attitudes in the selection of birth attendants, family income according to the minimum wage in the selection of birth attendants, and long distances from the reach of health services. The results of the chi-square test obtained a relationship between knowledge (0.002), attitude (0.001), family income (0.020) and reach of health services (0.034) with the selection of birth attendants. It is suggested that the Kampar Kiri Hulu I Health Center in Kampar Regency needs to increase access to health services, increase health education, and provide guidance to traditional birth attendants.